Psychological Well-Being Dewasa Awal dengan Disabilitas Fisik yang Mengalami Perceraian Orang Tua - Putri, Asia Nawita; Niken Widi Astuti (Psikodinamika: Jurnal Literasi Psikologi, 2025)
Psychological well-being is an individual's ability to make meaning of life, have a satisfied life,a view of the problems that occur in life and a balance between positive and negative feelings.The consequences of parental divorce that occur and physical disabilities experienced by earlyadults can affect the achievement of psychological well-being. The purpose of this study was todetermine the description of psychological well-being in early adults with physical disabilitieswho experienced parental divorce in childhood. This study uses qualitative methods with datacollection techniques in the form of observation and interviews. There are three participants inthis study. Based on the results of the analysis, one of the three participants did not have goodpsychological well-being because only three of the six dimensions were fulfilled.